Lipid Solubility and Molecular Weight: Whose Idea Was That - Kasting, G.B. (Skin pharmacology and physiology, 2013)
Gene Cooper was a bright theoretician, a skilled product developer, and a motivational leader who applied his talents to the skin science area early in his career. His work led to the development of finite dose skin absorption models, chemical penetration enhancer technologies and quantitative structure-penetration relationships for chemicals contacting human skin. His ideas regarding the impact of molecular weight and lipid solubility on skin transport catalyzed the later development by Potts and Guy of the first successful skin permeability model. But Gene's most important contribution to the field was as a scientific role model and an inspirational leader who launched the careers of several young scientists, including the author of this article.